Governing for inclusion:local government, mobility, and community creation - Mapitsa, Caitlin Blaser (My University, 2019)
This thesis considers the ways through which migrants and local government officials co-create communities through their engagement with each other. With a recent upsurge of populist trends limiting migration globally, while inequality continues to increase, South Africa’s experiences in managing diverse communities provide important lessons for scholars trying to understand both the drivers and limits of these trends. Through six related publications, this thesis suggestions that local governmnet officials and migrants are both playing active roles in defining communities and manufacturing categories of difference. Municipal officials often bring an epistemological bias towards a sedentary population, while migrants respond by demonstrating contestation of local authority and geographic boundaries.First, a diagnostic tool that maps the nexus between mobility and local governance is presented in the thesis. The next article problematises this mapping by discussing some of the methodological and conceptual complexities that must be considered when bringing the two areas together. Then, the thesis considers in more detail one dimension of the diagnostic – specifically, the use of data to plan towards mobility. The following article looks at how perceptions of municipal officials are driving practice in responding to migrants. In chapter seven, municipal spatial management practices will be considered in relation to migration, particularly given that the Spatial Planning and Land Use Management Act has recently given widespread autonomy to municipalities to manage land use. Chapter eight looks at political incentives around exclusion and xenophobia. Finally, the thesis is concluded by a discussion and conclusion chapter, which discusses the results as a whole, synthesizes key theoretical findings, and looks at implications for future research. The research informing each of the six articles draws on empirical research from five South African municipalities in Gauteng, Limpopo, and Mpumalanga, in addition to work previously done by ACMS at the municipal level. This research considers localised experiences of migration management outside of the more widely studied mega cities and border areas. This thesis has found that municipal practice has a profound influence on the management of migration. In fact, municipalities are mandated to manage spheres that are critical to migration, such as land use and transport hubs. The findings of this research make a strong case for why policy making at a municipal level should be considered with a lens of migration just as much as international relations and other more traditional migration policy arenas.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree Doctor of Philosophy (PhD), University of the Witwatersrand, Johannesburg, 2019